Perspectives of pregnant women during the COVID-19 pandemic: A qualitative study. Issue 3 (May 2022) - Atmuri, Kiran; Sarkar, Mahbub; Obudu, Efe; Kumar, Arunaz
Abstract: Background: The current COVID-19 pandemic has been shown to have profound effects on pregnant women globally, particularly, on their psycho-social wellbeing. Despite this, there has been limited qualitative inquiry into the experiences of pregnant women during the pandemic. Aim: This original research aimed to study the perspectives of pregnant women in Australia in relation to the impact of the COVID-19 pandemic on their pregnancy experience. Methods: A qualitative descriptive study design with semi-structured interviews was adopted. The study was performed in Melbourne, Australia. A total of fifteen interviews were conducted. Data was analysed thematically to develop major themes and subthemes. Results: A total of four major themes were developed: support for a positive experience, impact on preparedness in pregnancy and beyond, facing uncertainty of a pandemic, and retaining resilience and optimism. Conclusions: The COVID-19 pandemic has affected the experience of pregnant women with potential to compromise their psycho-social wellbeing. The major themes identified in this study offer insight to organisations to develop woman-centred care during the pandemic and optimise the psycho-social wellbeing of pregnant women.